2021
DOI: 10.3390/nu13113989
|View full text |Cite
|
Sign up to set email alerts
|

Preventive Effect and Molecular Mechanism of Lactobacillus rhamnosus JL1 on Food-Borne Obesity in Mice

Abstract: Probiotics can prevent obesity and related metabolic complications. In our study, the protective effect and molecular mechanism of Lactobacillus rhamnosus JL1 (separated from the feces of healthy infants) on high-fat diet mice were investigated. After 10 weeks of dietary intervention with L. rhamnosus JL1 intervention, the body weight of the JL1 group (23.78 g) was significantly lower than that of the HFD group (26.59 g, p < 0.05) and the liver index was reduced. Serum biochemical analysis showed that the T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 45 publications
2
13
0
Order By: Relevance
“…Previous studies have shown that LPS-induced inflammation is one of the causes of pancreatic beta cell dysfunction [42], which also explains why the DM mice had the most severe inflammation and structural abnormalities of tissues. Liver steatosis in the DM group can be explained by the excess accumulation of these lipid metabolites [43].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that LPS-induced inflammation is one of the causes of pancreatic beta cell dysfunction [42], which also explains why the DM mice had the most severe inflammation and structural abnormalities of tissues. Liver steatosis in the DM group can be explained by the excess accumulation of these lipid metabolites [43].…”
Section: Discussionmentioning
confidence: 99%
“…LPS can penetrate through the intestinal epithelial cells and, after binding to chylomicrons, are transported to insulin-sensitive organs, causing insulin resistance and inflammation [ 72 ]. One of the main characteristics of type 2 diabetes is chronic inflammation; patients with this condition present excessive levels of inflammatory markers [ 73 ]. The levels of these pro-inflammatory elements were linked to those of LPS and free fatty aciyesds and are considered the important link between inflammation, obesity, insulin resistance, and type 2 diabetes.…”
Section: Use Of Probiotics For Pharmaceutical Propertiesmentioning
confidence: 99%
“…Diabetic mouse models have shown acute inflammation and structural abnormalities in their tissues. Fatty liver disease steatosis was also shown in the diabetic group due to the excessive accumulation of lipid metabolites [ 73 ].…”
Section: Use Of Probiotics For Pharmaceutical Propertiesmentioning
confidence: 99%
“…Acetic acid is a very important raw material for the synthesis of serum total cholesterol (TC) and participates in the hepatic circulation, thus regulating lipid metabolism disorders ( 73 ). Propionic acid inhibits the synthesis of TC.…”
Section: Key Mechanisms Involved In the Regulation Of Intestinal Micr...mentioning
confidence: 99%